OPTIMALISASI PENGGUNAAN TEKNOLOGI INFORMASI DALAM PENATAUSAHAAN ASSET/ BARANG MILIK DAERAH - Rachmawati, Rima; Arwati, Dini; Herawati, Shinta Dewi; Arnan, Sendi Gusnandar (Jurnal ASET (Akuntansi Riset), 2018)
The purpose of this study is to find out the effect of the use of information technology in the administration of Assets. Asset management is not just administrative but more than an asset manager's effort to improve efficiency, effectiveness and increase asset added value assets itself. Government regulations regulate asset management through the use of information technology in the administration of assets, including bookkeeping, inventory and reporting activities. This research was conducted in the regional government work unit of Garut Regency which has implemented the Regional Goods Cycle Information Technology Application (ATISISBADA). The results of the study concluded that the optimal use of information technology in the ATISISBADA application was able to increase the effectiveness of assets administration activities. The implications of the results of this study are efforts to solve the problems that occur, namely optimizing the use of ATISISBADA in asset management activities in regional government.